Effectiveness of deep electroacupuncture with strong deqi and shallow electroacupuncture with no deqi for lumbar disk herniation: study protocol for a randomised controlled trial. Issue 11 (11th November 2020) - Huang, Ziling; Zhao, Jianxin; Pei, Xinghong; Wang, Bobo
Abstract : Introduction: Lumbar disk herniation (LDH) is a common cause of low back pain and dysfunction. Studies have shown that electroacupuncture (EA) can achieve pain relief in patients with LDH. However, there is a lack of evidence regarding the effectiveness of deep EA with strong deqi and shallow EA with no deqi in patients with LDH. This study aims to evaluate the effectiveness of deep EA with strong deqi and shallow EA with no deqi in the treatment of LDH. Methods and analysis: In this randomised controlled trial, patients with LDH who have low back pain with or without radiculopathy for at least 12 weeks will be enrolled. In total, 44 patients will be recruited from the Third Affiliated Hospital of Beijing University of Chinese Medicine, Beijing, China. Patients will be randomised into the deep EA group and the shallow EA group in a ratio of 1:1 and will be administered 12 sessions of EA treatment (three times a week for 4 weeks, 20 min for each session). The follow-up duration will be 4 weeks. Low back pain intensity and leg pain intensity (in patients with radicular pain) measured using the Visual Analogue Scale (VAS) will be assessed as the primary outcomes. Function (measured using the Roland-Morris Disability Questionnaire), quality of life (measured using the EuroQol Five-Dimensional Five-Level Questionnaire) and patient-evaluated therapeutic effect will be assessed as the secondary outcomes. Patients' expectations of EA, the success of the blinding method and safety will also be evaluated. Statistical analyses will be followed by the intention-to-treat analysis. Ethics and dissemination: This study was approved by the Ethics Committee of the Third Affiliated Hospital of Beijing University of Chinese Medicine (approval number: 2019-XS-ZB06). Study results will be disseminated through publication in an open access journal. Trial registration number: ChiCTR-1900026518.